2012
DOI: 10.1039/c2ce25470k
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of low-melting ionic transition-metal complexes with N-alkylimidazole ligands

Abstract: Visit the CrystEngComm website for more cutting-edge crystal engineering research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 30 publications
(47 reference statements)
0
29
0
Order By: Relevance
“…Furthermore, since the cathodic breakdown reaction of the ionic liquid is the desired electrodeposition of the metal, uncontrolled decomposition products are not formed (provided that a sacrificial anode is being used), making the electrolyte bath more sustainable. Several ionic liquids that can be considered as liquid metal salts have been reported in the literature, 11,12 including those containing silver(I), 13,14 copper(I) 15 and copper(II), 16,17 and cobalt(II). 18 Electrodeposition from this type of compounds has been described.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since the cathodic breakdown reaction of the ionic liquid is the desired electrodeposition of the metal, uncontrolled decomposition products are not formed (provided that a sacrificial anode is being used), making the electrolyte bath more sustainable. Several ionic liquids that can be considered as liquid metal salts have been reported in the literature, 11,12 including those containing silver(I), 13,14 copper(I) 15 and copper(II), 16,17 and cobalt(II). 18 Electrodeposition from this type of compounds has been described.…”
Section: Introductionmentioning
confidence: 99%
“…21 Ionic liquids comprising a metal cation that is coordinated by several neutral ligands such as acetonitrile or N-alkylimidazoles and charge balanced by non-or weakly coordinating anions such as Tf2N are liquid metal salts with low melting points. [22][23][24][25] The incorporation of the metal in the cation of the liquid metal salt makes it easier to electrodeposit the metal on the negatively charged cathode. [22][23][24][25] Metal bis(trifluoromethylsulfonyl)imides have also been used as Lewis acid catalyst in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] The incorporation of the metal in the cation of the liquid metal salt makes it easier to electrodeposit the metal on the negatively charged cathode. [22][23][24][25] Metal bis(trifluoromethylsulfonyl)imides have also been used as Lewis acid catalyst in organic synthesis. [26][27][28][29][30][31] For example, Suzuki et al found that Yb(Tf2N)3 catalyzed Michael reactions of beta-ketoesters 27 and Duris et al showed that La(Tf2N)3 acted as catalysts for Friedel-Crafts acylations.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few examples of these "liquid metal salts" can be found in the literature, 4,5,6,7 and their use for electrochemical purposes has only been rather scarcely investigated. 8,9,10,11,12,13,14 Our research group recently pointed to the potential of these liquid metal salts as electrolytes for the high-rate electrodeposition of copper, 15,16,17 and silver.…”
Section: Introductionmentioning
confidence: 99%